THE BENEFIT AND WEAKNESS OF ORAL EXAMINATION IN MEDICAL EDUCATION - Rika Lisiswanti (JUKE Unila, 2014)
Oral examination was abandoned because a lot of low validity and reliability by many countries around the world who are applying these methods to assess student competency. In Indonesia, there are still many faculty who apply this method in both the stage assessment undergraduate and clinical rotation phase. In this article, we will discuss the existence of an oral examination in medical education. More emphasize at the validity and reliability of oral examination so that it can be accepted as a method that is believed to assess the ability of students in medical education.  Experts of medical education have conducted a study by modifying the traditional oral examination to be more valid and realeabel, example: structured oral examination. Oral examination can still be used as a method of the assessment in medical education and it’s  depends on the policy of institution [JuKe Unila 2014; 4(8):233-239]